(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To update the current advances and recommendations on anesthesia for Transcatheter Aortic Valve Implantation (TAVI/TAVR), thereby proposing a strategy for selecting the appropriate anesthesia method in clinical practice. Methods: Information was collected from articles on PubMed, Cochrane Library using the keywords “Transcatheter Aortic Valve Implantation/Replacement” or “TAVI” or “TAVR” AND “anesthesiologic management” or “sedation” or “general anesthesia” or “local anesthesia”. The available evidence regarding anesthesia for TAVI/TAVR procedures was synthesized and analyzed to propose clinical application guidelines. Results: Local anesthesia (LA) combined with conscious sedation (CS), as well as LA alone, are currently predominant compared to general anesthesia (GA). GA still plays an important role in cases involving alternative vascular access, complex procedures (difficult valve-in-valve), uncooperative patients, or hemodynamically unstable patients. Conclusion: LA + CS or LA alone should be the preferred choice for most TAVI/TAVR cases performed via the femoral artery approach. The anesthesia selection strategy for TAVI/TAVR procedures needs to be individualized and based on the evaluation of the Heart Team.